Problematika Guru Pendidikan Agam Islam (Pai) Dalam Menyusun Soal Berbasis Higher Order Thinking Skill (HOTS) Di SMP Negeri 2 Palu - Siti Rahma; Erniati Erniati; Hamlan Hamlan (Journal on Education, 2024)
This study aims to find out the problems faced by teachers and find out solutions for teachers who experience problems in compiling problems based on Higher Orther Thinking Skill (HOTS) or high-level thinking skills. This study uses qualitative research methods to understand a condition that occurs in PAI teachers in compiling HOTS questions. The results of this study show that the problems faced by PAI teachers in compiling Higher Thinking Skill (HOTS) questions at SMP Negeri 2 Palu have various problems. There are two problems with the three PAI teachers, namely first, the difficulty in compiling questions that contain problem solving. Second, PAI teachers have problems in determining the KKO (Operational Verb) that is appropriate and in accordance with Bloom's Taxonomy. Another problem is caused by the age factor experienced by one of the elderly PAI teachers resulting in decreased competence so that it is difficult to understand high-level problem solving. This research confirms that the school should conduct workshops related to the preparation of HOTS questions for teachers at SMP Negeri 2 Palu more often. As for PAI teachers, they should always improve their competence in compiling HOTS questions by utilizing the internet, social media and relevant books. In addition, PAI teachers should seriously participate during the Workshop and MGMP activities, so that the knowledge and information obtained can be truly understood and applied in the preparation of HOTS questions.